Retrieval Deficiency in Brain Activity of Working Memory in Amnesic Mild Cognitive Impairment Patients: A Brain Event-Related Potentials Study - Li, Bin-Yin; Tang, Hui-Dong; Chen, Sheng-Di (Frontiers in Aging Neuroscience, 2016)
In the early stage of Alzheimer disease (AD) or mild cognitive impairment (MCI), working memory (WM) deficiency is prominent and could be attributed to failure in encoding, maintenance or retrieval of information. However, evidence for a retention or retrieval deficit remains equivocal. It is also unclear what cognitive mechanism in WM is impaired in MCI or early AD. We enrolled 46 subjects from our Memory Clinics and community, with 24 amnesic MCI patients and 22 normal subjects. After neurological and cognitive assessments, they performed a classic delayed match to sample (DMS) task with simultaneous event-related potential (ERP) recorded. The ERPs in encoding and retrieval epoch during WM were analyzed separately. The latency and amplitude of every ERP component were compared between two groups, and then analyzed to explore their relationship with neuropsychological performance. Finally, the locations of maximal difference in cortex were calculated by standard low-resolution tomographic analysis. A total of five components were found: P1, N1, P2, N2, and P300. The amplitude of P2 and P300 was larger in normal subjects than in MCI patients only during retrieval, not encoding epoch, while the latency did not show statistical difference. The latency and amplitude of P1 and N1 were similar in two groups. P2 amplitude in the retrieval epoch positively correlated with memory test (auditory verbal learning test) and visual spatial score of Chinese Addenbrooke's Cognitive Examination-Revised (ACE-R), while P300 amplitude correlated with ACE-R. The activation difference in P2 time range was maximal at medial frontal gyrus. However, the difference in cortex activation during P300 time range did not show significance. The amplitude of P2 indicated deficiency in memory retrieval process, potentially due to dysfunction of central executive in WM model. Regarding the location of P2 during WM task, medial frontal plays important role in memory retrieval. The findings in the present study suggested that MCI patients have retrieval deficit, probably due to central executive based on medial frontal gyrus. Thus, it may provide new biomarker for early detection and intervention for aMCI.